Utility of transperineal template-guided mapping prostate biopsy in biopsy-naïve men with PI-RADS 1-2 on multiparametric magnetic resonance imaging - Jong Hoon Lee; Chung Un Lee; Wan Song; Minyong Kang; Hyun Hwan Sung; Byong Chang Jeong; Seong Il Seo; Seong Soo Jeon; Hwang Gyun Jeon (Prostate International, 2024)
Objective: To analyze the outcomes of transperineal template-guided mapping biopsy (TTMB) in biopsy-naïve men with multiparametric magnetic resonance imaging (mpMRI) results of Prostate Imaging-Reporting and Data System (PI-RADS) 1-2. Patients and methods: We retrospectively reviewed TTMB outcomes in biopsy naïve patients with PI-RADS 1-2 at a single center from August 2018 to May 2023. The patients' clinicopathologic data were reviewed, clinically significant prostate cancer (csPCa) detection rates were identified. We determined significant predictive factors and determined those optimal cutoff point using receiver operating characteristic (ROC) curves. Results: 255 biopsy naïve patients with PI-RADS 1-2 underwent TTMB. 72 (28.2%) were diagnosed with prostate cancer and 30 (11.8%) were diagnosed with csPCa. ROC curves were used to identify predictive factors for diagnosing csPCa. Age (area under ROC curve [AUC]: 0.74, 95% CI: 0.65–0.83, P < 0.001) and prostate specific antigen density (PSAD) (AUC: 0.63, 95% CI: 0.53–0.72, P = 0.025) were significant predictive factors, and the optimal cutoff points determined using the Youden index were 65 years and 0.15 ng/mL/mL, respectively. Conclusion: Of biopsy-naïve patients classified as PI-RADS 1–2, 11.8% were diagnosed with csPCa, and we identified age and PSAD as significant predictive factors. Our study will help determine the biopsy method for patients with PI-RADS 1–2 without biopsy experience.